The Differential Effects of Uphill Sprint and Side Jump Sprint Exercises and Various Anthropometric Characteristics on the Speed of Soccer Players - I Dewa Made Aryananda Wijaya Kusuma; Nining Widyah Kusnanik; Ria Lumintuarso; Fakhrur Rozy; Yanyong Phanpheng; Donny Ardy Kusuma (OVS LLC, 2023)
Study purpose. To increase the running speed of soccer players, anthropometric factors need to be considered when choosing a training model. Materials and methods.  The experimental method with a 2 x 3 factorial design was used in this study. Purpose random sampling technique was used to select a sample of 60 participants from a population of 100 people. Then the sample was divided into six groups using a stratified random sampling technique (large UHS, n=10 participants; moderate UHS, n=10 participants; small UHS, n=10 participants; large SJS, n=10 participants; moderate SJS, n=10 participants; small SJS, n=10 participants). The 20-meter running speed test and anthropometric measurements were used as data collection instruments. Data analysis uses a two-way ANOVA and normality and homogeneity tests as prerequisites. Results. The results of the study found that there were significant differences in the two training models with a Sig value of 0.002<0.05, there were significant differences in the three anthropometric groups with a Sig value of 0.000<0.05, andthere was an interaction between the training model and anthropometric characteristics in increasing the 20-meter running speed with a Sig value of 0.001<0.05. Conclusions. This study concluded that the SJS training model was suitable for three levels of anthropometric ratios, while UHS was very suitable for small ones. Another conclusion was that the small anthropometric ratio had the greatest effect on the speed of the 20-meter sprint.